PEMENUHAN HAK KORBAN TINDAK PIDANA TERORISME BERDASARKAN UN BASIC PRINCIPLES AND GUIDELINES 2005 - Zeruya Hosiana; Andrey Sujatmoko (Faculty of Law, Universitas Trisakti, 2023)
This study discusses the fulfillment of the rights of victims of terrorism criminal acts based on the UN Basic Principles and Guidelines 2005 regarding the case of KKB Papua against health workers on Kiwirok District, Papua in 2021. There are two main issues, they are whether victims of terrorism criminal acts have the right to obtain remedy based on the UN Basic Principles and Guidelines 2005, and how to implement the restoration of the rights of health workers as victims of terrorism criminal acts by KKB Papua in 2021 based on Law Number 31 of 2014 concerning Protection of Witnesses and Victims. The type of research used is normative with data processing carried out qualitatively in the form of descriptive analysis. The data source used is secondary data and conclusions are drawn deductively. Based on the results of the analysis, victims of criminal acts of terrorism have the right to receive remedy according to the UN Basic Principles and Guidelines 2005 based on Part III of the UN Basic Principles and Guidelines 2005. In practice, implementing the remedy of the rights of health workers as victims of criminal acts of terrorism by the Papua KKB in 2021 according to Law Number 31 of 2014 concerning Protection of Witnesses and Victims is not appropriate because the health workers and their families have not received compensation.